FERTILITY ENHANCING EFFECT OF Asparagus racemosus ROOT METHANOL EXTRACT ON ORNIDAZOLE-INDUCED SPERMATOTOXICITY IN MALE WISTAR ALBINO RATS - GREESHMA. V. JOHN; S. JUSTIN RAJ (The Bioscan, 2026)
Drug-induced spermatotoxicity and male infertility are significant issues related to reproductive health. In this work, male Wistar albino rats were exposed to ornidazole- induced spermatotoxicity, and the fertility-enhancing impact of Asparagus racemosus methanolic root extract was assessed. Thirty rats were split into five groups: extract-treated (50 and 100 mg/kg body weight), control, untreated, and standard drug-treated. Ornidazole (600 mg/kg body weight) was used to produce spermatotoxicity. While decreasing sperm DNA fragmentation, the extract markedly increased body weight, reproductive organ weight, sperm count, motility, viability, morphology, plasma membrane integrity, hematological parameters, and reproductive hormone levels. There was more protective action at the higher dosage. According to the study, Asparagus racemosus has important spermatoprotective and fertility-boosting qualities.